Risk aversion in the Eurozone - Jonathan Benchimol (Research in Economics, 2014)
We propose a New Keynesian Dynamic Stochastic General Equilibrium (DSGE) model where a risk aversion shock enters a separable utility function. We analyze five periods from 1971 through 2011, each lasting for 20 years, to follow over time the dynamics of several parameters such as the risk aversion parameter; the Taylor rule coefficients; and the role of the risk aversion shock in output, inflation, interest rate, and real money balances in the Eurozone. Our analysis suggests that risk aversion was a more important component of output and real money balance dynamics between 2006 and 2011 than it was between 1971 and 2006, at least in the short run.
Keywords: E23; E31; E51; D81; E44; E59; 330; Risk aversion shock; Output; Money; Eurozone; New Keynesian model; DSGE models; Bayesian estimation; Euro area; Role of money